2012
DOI: 10.3109/0886022x.2011.654145
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Biopsy-Proven Chronicity and End-Stage Renal Failure Associated with Oral Sodium Phosphate Solution

Abstract: Bowel purgatives containing oral sodium phosphate (OSP) solution are used frequently in general practice and they have the potential of causing acute kidney injury especially in patients with some identified risk factors. Kidney injury may lead to chronicity and end-stage renal disease. Here we present, with renal biopsy findings, an elderly patient suffering from end-stage renal failure due to OSP solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…()18/FIleus 11,600 (2 × 5,800 within 12 h)Haemodialysis remission Baseline: 0.41 Onset: 0.87–1.08 Follow‐up: 0.60 3 Cakar et al. ()65/MHypertension 11,600 (2 × 5,800 within 12 h)CKD. Patient started haemodialysis treatment Baseline: 1.14 Onset: 1.82 Follow‐up: 3.14 Kidney biopsy showed mild focal tubulointerstitial inflammation, tubular atrophy, sclerosis4Fine and Patterson ()84/FHypertension, mild cardiac insufficiency.…”
Section: Appendix P – Case Series and Case Reports After Acute Administrationmentioning
confidence: 99%
“…()18/FIleus 11,600 (2 × 5,800 within 12 h)Haemodialysis remission Baseline: 0.41 Onset: 0.87–1.08 Follow‐up: 0.60 3 Cakar et al. ()65/MHypertension 11,600 (2 × 5,800 within 12 h)CKD. Patient started haemodialysis treatment Baseline: 1.14 Onset: 1.82 Follow‐up: 3.14 Kidney biopsy showed mild focal tubulointerstitial inflammation, tubular atrophy, sclerosis4Fine and Patterson ()84/FHypertension, mild cardiac insufficiency.…”
Section: Appendix P – Case Series and Case Reports After Acute Administrationmentioning
confidence: 99%
“…This improves the consistency of the final product, upholds the weight and preserves the sensory characteristics (Goncalves, Rech, Rodrigues, & Pucci, 2008;Goncalves and Ribeiro 2008;Campden, 2012). Generally, polyphosphates are acknowledged as nontoxic, but some authors have observed that a high dietary introduction of these additives can cause hypocalcemia, renal injury with calcium phosphate accumulation in the kidneys (Weiner et al, 2001;Cakar et al, 2012). Impairment of the calcium-phosphorus ratio leads to certain hormonal disorders, while excess phosphates species interferes with calcium absorption in the gut, which results in the release of calcium from bones (Weiner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of clinically important adverse renal events after OSP use cannot be exactly quantified in the general or at-risk populations, since the majority of significant problems are drawn from relatively few (» 20) isolated case reports or case series of biopsy-confirmed APhN [7,50,52,67,80,[87][88][89][90]95,109,[111][112][113][114][115][116][117][118]121,122,124,128,129].…”
Section: Studies Evaluating the Risk Of Renal Impairment After Osp Usementioning
confidence: 99%